2013
DOI: 10.2147/ott.s54702
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Sonic Hedgehog signaling pathway genes indicates a risk of recurrence of breast carcinoma

Abstract: BackgroundAbnormal activation of the Sonic Hedgehog (SHH) signaling pathway contributing to carcinogenesis of some organs has been reported in the literature. We hypothesize that activation of the SHH pathway contributes to the recurrence of breast carcinoma.MethodsFifty consecutive patients with invasive breast carcinoma following curative resection were enrolled in this prospective study. The ratios of messenger RNA (mRNA) expression for Sonic Hedgehog (SHH), patched homolog-1 (PTCH-1), glioma-associated onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 39 publications
6
55
2
1
Order By: Relevance
“…Indeed, aberrant activation of Hh signaling has been observed in many aggressive cancers, in particular in cells exhibiting resistance to chemotherapy such as cancer stem cells or tumor‐initiating cells . The Hh receptor Patched, whose expression is induced upon activation of the Hh pathway, is overexpressed in many cancers such as lung, breast, prostate, ovary, colon, brain, melanoma and myeloid leukemia (see the Human Protein Atlas website http://www.proteinatlas.org/ENSG00000185920-PTCH1/cancer). Recent studies even suggested Patched as an early marker of gastric and thyroid cancers .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, aberrant activation of Hh signaling has been observed in many aggressive cancers, in particular in cells exhibiting resistance to chemotherapy such as cancer stem cells or tumor‐initiating cells . The Hh receptor Patched, whose expression is induced upon activation of the Hh pathway, is overexpressed in many cancers such as lung, breast, prostate, ovary, colon, brain, melanoma and myeloid leukemia (see the Human Protein Atlas website http://www.proteinatlas.org/ENSG00000185920-PTCH1/cancer). Recent studies even suggested Patched as an early marker of gastric and thyroid cancers .…”
Section: Introductionmentioning
confidence: 99%
“…These abnormal persistence or ectopic expression of Shh may stimulate an abnormal stem cell hyperplasia, a critical step in the neoplastic transition of these organs owing to its embryonic actions and mutagenic inflammation, though Shh relevant to inflammation varies by the cell/tissue type, location and overall environmental stresses. Regarding carcinogenesis, recent studies have implicated that continuous Shh signaling played a pathological role in the growth of various cancers such as medulloblastoma, basal cell skin carcinoma, squamous cell lung cancer, breast cancer, pancreatic cancer and CRC, where hedgehog was implicated in organogenesis and patterning of embryo during development stage . This is why, though Shh signaling is very critical to normal GI development, Shh has frequently been identified as target for GI cancers.…”
mentioning
confidence: 99%
“…Gli, Smo and PTCH were found to be overexpressed in HCC patients (Che et al 2012;Jeng et al 2013;Zhang et al 2013). Lu et al (2012) reported that Shh treatment can stimulate Hedgehog signaling to promote HCC cell invasion and migration by increasing GLI1 expression.…”
Section: Hedgehog Pathwaymentioning
confidence: 98%